Improving Students’ Vocabulary through “Word Square Method” - Astiantih, Susi (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2024)
Vocabulary refers to the set of words that a person is familiar with in a particular language. It includes words that an individual understands, recognizes, and can use in speaking, writing, listening, and reading. The question of the research was “How can word square method improve the students’ vocabulary?”. The objective of the research was to improve the students’ vocabulary at the first grade of SMP Negeri 1 Tanggetada. This research was a classroom action research that followed a particular set of actions, namely: preliminary research, planning, action, observing, analyzing and reflecting in each cycle. The aim of this research was to improve the students’ vocabulary mastery. The researcher used two instruments to obtain data, namely vocabulary tests that were administered on the fourth meeting of the first and second cycle, and observation sheets that were filled out throughout the meeting to observe the students’ behaviours during teaching and learning activities. The research resulted in significant improvement of the students' vocabulary mastery, as well as their activities in the classroom. There were two cycles in this research. The first cycle was failed because only 36% of the students were able to pass the minimum score (75)because the students did not yet understand the word square method. After the second cycle was implemented, and the researcher’s innovation in conducting word square in the classroom, 80% of the students were finally able to pass the minimum score which meant that the research was successful. Therefore, the research could be stopped.